Karakteristik Batupasir Formasi Dolokapa di Desa Dulukapa, Sumalata Timur, Gorontalo Utara - Ahmad, Artina; Permana, Aang Panji; Hutagalung, Ronal (Journal of Applied Geoscience and Engineering, 2025)
The research location is in the Dulukapa Area, East Sumalata District, North Gontalo Regency. This study aims to analyze the characteristics of Dulukapa Formation sandstone based on petrographic analysis. The research methods used are geological mapping and petrographic laboratory analysis. The results of the study indicate that the distribution of Dolokapa formation sandstone in the Dulukapa area is spread from west to east of Dulukapa Village. The type of sandstone is classified based on the results of gravel, sand, and clay calculations, namely Gravel Sandstone, Sandstone, and Muddy Sandstone. The results of the petrographic analysis indicate that the type of sandstone consists of Lithic Arenite and Lithic Graywacke.